Metallothionein: A Comprehensive Review of Its Classification, Structure, Biological Functions, and Applications - Ruoqiu Yang; Dumila Roshani; Boya Gao; Pinglan Li; Nan Shang (MDPI AG, 2024)
Metallothionein is a cysteine-rich protein with a high metal content that is widely found in nature. In addition to heavy metal detoxification, metallothionein is well known as a potent antioxidant. The high sulfhydryl content of metallothionein confers excellent antioxidant activity, enabling it to effectively scavenge free radicals and mitigate oxidative stress damage. In addition, metallothionein can play a neuroprotective role by alleviating oxidative damage in nerve cells, have an anticancer effect by enhancing the ability of normal cells to resist unfavorable conditions through its antioxidant function, and reduce inflammation by scavenging reactive oxygen species. Due to its diverse biological functions, metallothionein has a broad potential for application in alleviating environmental heavy metal pollution, predicting and diagnosing diseases, and developing skin care products and health foods. This review summarizes the recent advances in the classification, structure, biological functions, and applications of metallothionein, focusing on its powerful antioxidant effects and related functions.